Pengetahuan Remaja Putri Tentang Gangguan Menstruasi: Young Women Knowledge About Menstrual Disorder - Khayati, Fitriana Noor; Pujiastuti, Endah (Universitas Muhammadiyah Sidoarjo, 2016)
Menstruation disorders can decrease physical activity of teenager. The most common menstrual disorders occur at the beginning and end of the reproductive period is under the age of 19 and over the age of 39 years. Menstruation disorders need to know where the adolescent reproductive organs is very important in the development of subsequent health. Menstruation disorders experienced by adolescents mostly dysmenorrhoea. It was a descriptive research using simple random sampling. The sample in this study was 30 respondents from SMK 3 Muhammadiyah Klaten. Most of the respondents had menstruation abnormalities were 21 students (70%), the majority of respondents average experience menarche at age 14 as many as 10 students (33.3%) and most knowledge of young girls about menstruation disorders was good as many as 25 students (83.3%).